2016
DOI: 10.1103/physrevb.93.245143
|View full text |Cite
|
Sign up to set email alerts
|

Absence of giant spin splitting in the two-dimensional electron liquid at the surface ofSrTiO3(001)

Abstract: We reinvestigate the putative giant spin splitting at the surface of SrTiO3 reported by SantanderSyro et al. [Nature Mat. 13, 1085]. Our spin-and angle-resolved photoemission experiments on (001) oriented surfaces supporting a two-dimensional electron liquid with high carrier density show no detectable spin polarization in the photocurrent. We demonstrate that this result excludes a giant spin splitting while it is fully consistent with the unconventional Rashba-like splitting seen in band structure calculatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
1
26
1
Order By: Relevance
“…Recent experiments suggest the scenario with itinerant charge coming solely from the topmost SrO layer is at least plausible 12,15 . A higher oxygen vacancy formation rate has been observed in fractured STO crystals compared to annealed STO wafers, which suggests exposure of the SrO termination can increase the vacancy formation rate 15 . Additionally, modeling x-ray photoelectron spectroscopy data of the mixed Ti 3+ /Ti 4+ state fits a scenario with all the itinerant charge isolated to the topmost termination layer, but the authors of this study ultimately dismiss this model as nonphysical 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments suggest the scenario with itinerant charge coming solely from the topmost SrO layer is at least plausible 12,15 . A higher oxygen vacancy formation rate has been observed in fractured STO crystals compared to annealed STO wafers, which suggests exposure of the SrO termination can increase the vacancy formation rate 15 . Additionally, modeling x-ray photoelectron spectroscopy data of the mixed Ti 3+ /Ti 4+ state fits a scenario with all the itinerant charge isolated to the topmost termination layer, but the authors of this study ultimately dismiss this model as nonphysical 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The 2DEG on the surface of STO has been heavily studied using angle resolved photoemission spectroscopy (ARPES) 9-12, 14, 15 . Measurements have been carried out on the (001), (110) 16 and (111) 17 More generally, perovskite oxides are typically divided into sub-unit cell layers that play different roles, like an active layer that drives the physical phenomena of interest sandwiched between passive doping layers.…”
Section: Heterostructuresmentioning
confidence: 99%
“…Based on the analysis of the data it was concluded that the Rashba spin-orbit energy was on the order of 10 meV. There was some debate about the linear versus cubic nature of the effect, but it was suggested by Baumberger et al [54,55] that the size and momentum dependence of the surface spin-orbit term can be tied to the proximity of E F to avoided crossing points of the heavy and light bands. Surface rumpling and atomic displacements imply that the d xz /d yz orbitals now have a finite, oxygen mediated, overlap with the d xy orbitals [46,47].…”
Section: The Srtio 3 Surfacementioning
confidence: 99%
“…Their analysis of magnetotransport led them to advocate a cubic Rashba term as the cause of the observed weak antilocalization behavior with a strength of about 0.5 meV, one order of magnitude less than reported in the above measurements. The low value of the carrier concentration (3 -8×10 12 cm −2 ) could explain both the cubic-like term and the discrepancy in the determination of its size [55]. The tunability of the Rashba contribution as well as its magnitude allows one to envisage spintronic applications, exploiting for example the so-called inverse Edelstein effect [44].…”
Section: The Srtio 3 Surfacementioning
confidence: 99%
“…The electronic structure has been revealed by angle‐resolved photoelectron spectroscopy (ARPES). The highest spectroscopic resolution is obtained at low temperature, typically 10 to 20 K . This allows to resolve 2D and 3D band character, calculate the Fermi surface (FS) volume, and estimate the electron effective mass.…”
Section: Introductionmentioning
confidence: 99%